Contraception, Sexuality and Pregnancy in Women with Psoriasis: Real-Life Experience of 235 Women - Maccari F; Fougerousse AC; Reguiai Z; Taieb C (Dove Medical Press, 2020)
François Maccari,1,2 Anne Claire Fougerousse,2,3 Ziad Reguiai,2,4 Charles Taieb5,6 1Private Practice, La Varenne St Hilaire, Paris, France; 2Reso Pso, Dermatologist Network, Paris, France; 3Military Teaching Hospital Bégin, Saint Mandé, Paris, France; 4Service De Dermatologie, Polyclinique Courlancy, Reims, France; 5FIMARAD, Hôpital Necker Enfants Malades, Paris, France; 6European Market Maintenance Assessment, Vincennes, Paris, FranceCorrespondence: Charles Taieb Email charles.taieb@emma.clinicBackground: Little is known about how women of childbearing age with psoriasis experience contraception, sexuality and pregnancies through the lens of their skin condition.Objective: To evaluate the experiences and expectations in this group of patients.Materials and Methods: In total, 235 women aged between 18 and 45 years old completed an online survey. We collected the characteristics of psoriasis, contraception and pregnancy history. Psoriasis severity was measured using the Simplified Psoriasis Index. Patient quality of life was assessed using the Dermatology Life Quality Index (DLQI) and the Short Form-12.Results: Psoriasis was mild in 78% of cases. The mean DLQI score was 8.8, highlighting a moderate impact of psoriasis. In total, 28% of the women had no current follow-ups, while at least two distinct physicians followed 21% of these patients. In total, 31.5% of the women felt that they could discuss sexuality during their consultations. In addition, 63% of respondents had a contraceptive method, but more than half of the women reported that contraception was rarely or never discussed during the consultations. In total, 63% had at least one pregnancy, and 61.5% reported that the doctor managing their psoriasis did not discuss their pregnancy during consultations. Psoriasis worsened during pregnancy for 21% of the respondents but improved in 34%. Among women who were not pregnant, less than 15% reported that the doctor in charge of their psoriasis discussed family planning and pregnancy possibilities.Conclusion: Our study shows that the management of women of childbearing age with psoriasis must be improved with respect to sexuality, contraception and pregnancy planning.Keywords: psoriasis, women, childbearing